Personalization of education in the context of psychological safety of students’ personality during the adaptation period - Kostina, Liubov M.; Nikolaeva, Anastasia V. (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика)
Introduction. The relevance of the article is determined by the state strategy of individual development of the younger generation, the orientation of the modern education system to personalized learning. Theoretical analysis allowed us to conclude that in the last decade there has been an increase in the interest of the scientific community in the problem of personalization of young people education and ensuring psychological safety of the individual. At the same time, the topic of psychological safety of students' personality remains insufficiently studied. The empirical analysis consisted in determining the specifics of psychological safety manifistation of first-year students' personality during their adaptation period. The study involved first-year students (n = 349) of higher educational institutions of the North-West region of the Russian Federation, aged 17–18 years, 72% girls, 28% boys. To assess the components of students’ personality safety and the level of their adaptation to learning, a set of diagnostic methods was used that meet the requirements of scientificity, reliability and validity. Based on the results of the study, the manifistation features of psychological safety components of the personality of first-year students with a higher level of adaptation to learning were revealed. Conclusion. Statistical analysis of empirical data allows us to state that students with a higher adaptation level have significant differences (from p = 0.05 to p = 0.001) in all components of psychological security of the individual: resistance, stability, security and efficiency of activity.